Avaliação das alterações vestibulares em crianças e adolescentes - Farias, Vanessa Vieira (2023)
Dizziness and vertigo are common symptoms in childhood but are often overlooked because they are believed to be symptoms associated only with adulthood diseases. As a result, diagnosing vestibular alterations in this age group is a challenge, leading to few records of dizziness in children and adolescents aged six to 17 years, justifying studies aimed at identifying, characterizing, and indicating exams and/or diagnoses of these alterations. This involves the development of two studies. The first study consists of evaluating screening instruments and is of an observational and cross-sectional nature. A questionnaire already validated for Brazilian Portuguese, the Dizziness Handicap Inventory (DHI), was used, as well as the Pediatric Visually Induced Dizziness Questionnaire (PVID), which was translated and cross-culturally adapted to Brazilian Portuguese. In the study, the PVID was applied along with the DHI. The second study involves a systematic review, with the guiding question being: what parameters are used for Vestibular Evoked Myogenic Potential (VEMP) testing in children? The first survey included children aged 6 to 17, divided into two groups: one with complaints of dizziness and one without. As a reference test, vectoelectronystagmography (VENG) was performed, including oculomotor tests and the caloric test. Significant differences in scores on both questionnaires between the two groups, as well as in the results of the VENG, were observed. Correlation tests and group difference analysis were used for the analysis. The systematic review was conducted from April to May 2022, with an update in April 2023. Electronic searches were conducted in the MEDLINE (via Pubmed), EMBASE, ScienceDirect, Scopus, as well as LILACS and SciELO databases. Based on this review, a protocol for performing VEMP in children was developed.